Inhibition of ethylene involved in resistance to E. turcicum in an exotic-derived double haploid maize population - Lipps, Sarah; Lipka, Alexander E.; Mideros, Santiago; Jamann, Tiffany (Frontiers in Plant Science, 2023)
Northern corn leaf blight (NCLB) is an economically important disease of maize. While the genetic architecture of NCLB has been well characterized, the pathogen is known to overcome currently deployed resistance genes, and the role of hormones in resistance to NCLB is an area of active research. The objectives of the study were (i) to identify significant markers associated with resistance to NCLB, (ii) to identify metabolic pathways associated with NCLB resistance, and (iii) to examine role of ethylene in resistance to NCLB. We screened 252 lines from the exotic-derived double haploid BGEM maize population for resistance to NCLB in both field and greenhouse environments. We used a genome wide association study (GWAS) and stepwise regression to identify four markers associated with resistance, followed by a pathway association study tool (PAST) to identify important metabolic pathways associated with disease severity and incubation period. The ethylene synthesis pathway was significant for disease severity and incubation period. We conducted a greenhouse assay in which we inhibited ethylene to examine the role of ethylene in resistance to NCLB. We observed a significant increase in incubation period and a significant decrease in disease severity between plants treated with the ethylene * Chromosome ^ Single Nucleotide Polymorphism Resistance to diseased leaf area (DLA) is genetically distinct from incubation period; a single marker was significant on chromosome 2 (Figure 3c). The significant marker, S2_10777410 (p = 0.053), is proximal to GRMZM2G068982, a methionine aminopeptidase.Using the same marker dataset, a stepwise regression approach did not reveal any significant